Intergovernmental dynamics in responding to COVID-19 in English and Australian cities - Broadhurst, K; Gray, N; Mykhnenko, V; Steane, E (Oxford University Press, 2022)
This comparative study, conducted at the height of the COVID-19 pandemic, explores how the contrasting governance systems in Australia and England responded to complex and rapidly evolving problems presented by the crisis. Comparing how national and local governments worked together and alongside other forms of subnational governance, the findings highlight the efficacy of multi-scalar governance arrangement in Australia over the fragmented, overly-centralised and inconsistent arrangements in England. As nations plan their recovery paths from the economic and social challenges of the crisis, the findings encourage a reset of spatial policy towards one that values and resources greater decentralisation and place-based recovery.